The Strength of Direct Ties: Evidence from the Electronic Game Industry - Jörg Claussen; Oliver Falck; Thorsten Grohsjean (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2010)
We analyze the economic effects of a developer's connectedness in the electronic game industry. Knowledge spillovers between developers should be of special relevance in this knowledge-based industry. We calculate measures for a developer's connectedness to other developers at multiple points in time. In a regression with developer, developing firm, publishing firm, and time fixed effects, we find that the number of a developer's direct ties, i.e., common past experience, has a strong effect on both a game's revenues and critics' scores. The intensity of indirect ties makes no additional contribution to the game's success.
urn:nbn:de:bvb:19-epub-11745-6
Keywords: 650